Skating technique for the straights, based on the optimization of a simulation model - Allinger, T. L.; van den Bogert, A. J. (Medicine & Science in Sports & Exercise, 1997)
Although experimental data have been collected to determine the skating techniques of the fastest skaters in the world, the "ideal" skating technique has not been determined (i.e., stroke time, glide time, push-off velocity, and push-off direction). The purpose of this study was to determine the skating technique that results in the fastest steady-state speed on a straight-away using optimization of a simulation model. A dynamic model of a skater was developed that included anatomical and physiological constraints: leg length, instantaneous power, and average power of a skater. Results from the model demonstrate that a number of skating techniques can be used to achieve the same steady-state speed. Increasing the average power output of a skater raises the top skating speed and decreases the range of optimal skating techniques. Increasing instantaneous power output (i.e., increasing isometric strength) increases the range of techniques a skater may use for a given speed. In the future, this model can be applied to individual skaters to determine if changes in technique or if improvements in power production are necessary to improve their steady-state skating speed. This model may be adapted to skating sports, such as speed skating, in-line skating, hockey, and cross-country skiing.